Enhanced Optical Transmission through MacEtch‐Fabricated Buried Metal Gratings. Issue 7 (8th December 2015) - Liu, Runyu; Zhao, Xiang; Roberts, Christopher; Yu, Lan; Mohseni, Parsian K.; Li, Xiuling; Podolskiy, Viktor; Wasserman, Daniel
Abstract : Metallic films with subwavelength apertures, integrated into a semiconductor by metal‐assisted chemical etch (MacEtch), demonstrate enhanced transmission when compared to bare semiconductor surfaces. The resulting "buried" metallic structures are characterized spectroscopically and modeled using rigorous coupled wave analysis. These composite materials offer potential integration with optoelectronic devices, for simultaneous near‐uniform electrical contact and strong optical coupling to free space.